Nitric oxide synthase inhibitors: a review of patents from 2011 to the present. (January 2015) - Yang, Yanyan; Yu, Tao; Lian, Yu-ji; Ma, Rujun; Yang, Sungjae; Cho, Jae Youl
<x xml:space="preserve">Abstract</x> Introduction: Nitric oxide synthases (NOSs) are a family of enzymes that play an essential role in synthesizing nitric oxide (NO) by oxidizing l-arginine. As previously reported, NO is a significant mediator in cellular signaling pathways. It serves as a crucial regulator in insulin secretion, vascular tone, peristalsis, angiogenesis, neural development and inflammation. Due to its important role, the inhibition of these vital enzymes provides, as tools, the opportunity to gain an insight into potential therapeutic applications targeting NOSs. Areas covered: This paper reviews the patent literature between 2011 and mid-2014 that specified inhibitors of NOS family members as the significant targets. Google and Baidu search engines were used to find relevant patents and clinical information using NOSs or NOS inhibitor as search terms. Expert opinion: Considerable recent progress has been made in the development of NOS inhibitors with pharmacodynamic and pharmacokinetic properties, and such development is likely to continue. The patented compounds attenuated mostly embodying evidence from in vitro and in vivo trials that demonstrate good potential for future clinical human trials and industrial applications. Furthermore, new techniques such as X-ray ligand crystallographic study and structure–activity relationship were popularly utilized, which give new insights for developing novel, safe, efficient and selective NOS inhibitors.